Bronchoalveolar-Lavage-Derived Fibroblast Cell Line (B-LSDM7) as a New Protocol for Investigating the Mechanisms of Idiopathic Pulmonary Fibrosis - Laura Bergantini; Miriana d’Alessandro; Sara Gangi; Dalila Cavallaro; Giuseppe Campiani; Stefania Butini; Claudia Landi; Luca Bini; Paolo Cameli; Elena Bargagli (Cells, 2022)
Background: The use of BAL to study ILDs has improved our understanding of IPF pathogenesis. BAL fluid is routinely collected and can be considered a clinical and research tool. The procedure is well tolerated and minimally invasive. No specific cell lines from BAL or immortalized cell lines from IPF patients are available commercially. A method to quickly isolate and characterize fibroblasts from BAL is an unmet research need. Materials and methods: Here we describe a new protocol by which we isolated a cell line from IPF. The cell line was expanded in vitro and characterized phenotypically, morphologically and functionally. Results: This culture showed highly filamentous cells with an evident central nucleus. From the phenotypic point of view, this cell line displays fibroblast/myofibroblast-like features including expression of alpha-SMA, vimentin, collagen type-1 and fibronectin. The results showed high expression of ROS in these cells. Oxidative stress invariably promotes extracellular matrix expression in lung diseases directly or through over-production of pro-fibrotic growth factors. Conclusions: Our protocol makes it possible to obtain fibroblasts BAL that is a routine non-invasive method that offers the possibility of having a large sample of patients. Standardized culture methods are important for a reliable model for testing molecules and eventual novel development therapeutic targets.